Bowie - Critchley, Simon, 1960- (OR Books, 2014)
Critchley, whose writings on philosophy have garnered widespread praise, melds personal narratives of how Bowie lit up his dull life in southern England's suburbs with philosophical forays into the way concepts of authenticity and identity are turned inside out in Bowie's work.